Potensi Pengelolaan Wisata Edukasi Pabrik Gula Kebon Agung Di Kabupaten Malang Jawa Timur - Yohanes Hessel Salomo Patiung; Ida Ayu Suryasih (JURNAL DESTINASI PARIWISATA, 2022)
The Kebon Agung Sugar Factory has a lot of tourism potential that can be managed as an educationaltour. However, its tourism potential has not been managed properly because the Kebon Agung SugarFactory currently only focuses on carrying out the factory's main function, namely producing sugar. Sothat the potential for managing educational tourism at the Kebon Agung Sugar Factory is consideredimportant to be a guideline for the company in managing its educational tourism potential.This research uses qualitative methods, namely by conducting observations, interviews, anddocumentation studies. The technique of determining the informants used purposive sampling.Qualitative data were analyzed using descriptive qualitative analysis and using concepts of tourismpotential concepts, educational tourism concepts, tourist attraction concepts, tourism managementconcepts, sustainable tourism concepts and analyzed using SWOT analysis. The results of this researchindicate that the existing conditions of tourism potential at the Kebon Agung Sugar Factory are all managedto carry out and support the main functions of the factory activities. Every tourism potential of the KebonAgung Sugar Factory is analyzed using a SWOT analysis all of the tourism potential can be managed intoan educational tour of the Kebon Agung Sugar Factory.Keyword: Tourism Potential, Educational Tourism, Sugar Factory.